ANALISIS KINERJA ANGGARAN PEMERINTAH DAERAH SEBELUM DAN SAAT PANDEMI COVID-19 - Rizka Wilda Kausari; Rita Meutia; Rudy Fachruddin (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2022)
This study aims to determine the budget performance of local city governments throughout Indonesia in the Regional Revenue and Expenditure Budgets before and during the Covid-19 pandemic. This research was conducted in 93 municipal governments. The method used in this research is descriptive quantitative and the different Wilcoxon Signed Rank Test to test differences in budget performance before and during the Covid-19 Pandemic. The results of the test are, that there is a difference between the budget performance of the regional income, the budget performance of the local Own-Source, and the budget performance of the transfer income, but there is no difference in the budget performance of the other legitimate regional income before and during the Covid-19 pandemic. Furthermore, there is no difference in the budget performance of the expenditure regional, the budget performance of the operational expenditure, and the budget performance of the transfer expenditure, but there are differences in the budget performance of the capital expenditure and the budget performance of the unexpected expenditure before and during the Covid-19 pandemic.